Post‐fire behavior of steel slag fine aggregate concrete - Zhuang, Xin; Liang, Yi; Ho, Johnny Ching Ming; Wang, Yu‐Hang; Lai, Mianheng; Li, Xuanyang; Xu, Zhenhai; Xu, Yuning (Structural concrete : journal of the FIB, 2022)
Using steel slag fine aggregate (SSFA) to replace river sand (RS) in making concrete offers a sustainable solution for mitigating the environmental issues owing to the large‐scale mining of RS and disposal of a large amount of steel slag. The mechanical behavior and chemical property of concrete made with SSFA at ambient temperature were investigated extensively. However, relatively few studies have been conducted to investigate the behavior of concrete with SSFA after exposure to elevated temperatures. To fill up this research gap, this paper studied the post‐fire behavior of five concrete mixes with SSFA replacing RS. The effect of SSFA replacement ratio by volume (0%, 25%, 50%, 75%, and 100%) on the heating temperature—time curve, color and appearance changes, weight loss, failure mode, and residual compressive strength of concrete under curing period of 28‐ and 91‐day, after exposure to 25 (ambient temperature), 400, 600, 800, and 1000°C was investigated. Besides, chemical composition at ambient and after exposure to elevated temperatures was analyzed with the aid of X‐ray diffraction. Test results showed that with SSFA partially or totally replacing RS, the heat insulation capability of concrete could be enhanced, especially at the replacement ratio of 75%. Moreover, concrete with RS replaced with SSFA presented larger or comparable residual strength after exposure to elevated temperatures from 600–800°C. Lastly, the design model by EC2 was adopted to predict the residual strength of concrete with and without SSFA. Comparing the design and measured residual strengths, it was concluded that EC2 was conservative.